Analysis of Hydrolyzed Collagen in Facial Serum for Halal Authentication Using FTIR Spectroscopy and Multivariate Calibration - Salamah, Nina; Firdaus, Rizqi Amalia; Guntarti, Any; Ahda, Mustofa; Uddin, Abm Helal; Kurniawan, Muhammad Fariez (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Cosmetic trends in Indonesia are on the rise, particularly for facial serum products. However, most of these products lack halal certification, posing an important concern for Muslim consumers due to the potential use of haram substances, such as pork gelatin. This study seeks to identify the source of gelatin in serum products using the Fourier Transform Infrared (FTIR) spectroscopy and chemometric analysis. The samples used in this study include a reference facial serum formulated with pure bovine and porcine gelatin concentrations in the ratios of 1:0, 8:2, 5:5, 2:8, and 0:1, three hydrolyzed collagen serums that are not yet labeled halal and available on Shopee, and one serum that is labeled halal. The method used was FTIR combined with PLS chemometrics and PCA. The isolation of facial serum gelatin was performed using acetone at -20oC, followed by analysis via FTIR at wave numbers ranging from 4000 to 400 cm-1. FTIR results indicated the presence of functional groups in gelatin constituents, including C O, N H, C N, and C H aliphatic. The wavelengths employed for PLS and PCA analysis ranged from 1631 to 1430 cm-1. Calibration results showed R2=0.9936 and RMSEC=3.0445%. Internal validation yielded RMSECV=0.1674% and R2=0.9994 whilst external validation yielded RMSEP=0.9981% and R2=0.9910. Lastly, PCA analysis revealed that one halal-labeled serum sample contained bovine gelatin, whereas the three examined commercial serums were free from both pork and bovine gelatin.